PERAN PENDIDIK DALAM PENGEMBANGAN DIRI PESERTA DIDIK di MTs AS’ADIYAH KECAMATAN SAMBOJA KAB. KUTAI KARTANEGARA - Anggranti, Wiwik (Al Tadib : Jurnal Ilmu Pendidikan, 2016)
This study examines the role of educators in casuistry in the development of self-learners. Plus selfimprovement is the ability of learners in complete competence in curriculum demands. The purpose of this study was to determine and describe the role of educators in the development of self-learners in the District As'adiyah MTs Samboja Kab. Kutai. With the model qualitative descriptive study, researchers sought to explore the field data as observers. The results showed that the role of educators as informator, motivator, organizer, director, initiator, transmitter, facilitators, mediators, evaluators quite familiar with their duties and carry out the task with the facilities and infrastructure that exist and the role of educators in the development of selflearners is very central though with facilities and infrastructure is very limited. Keywords: self-development, the role and duties of teachers